Thermogravitational convection of Al2O3-H2O nanoliquid in a square chamber with intermittent blocks - Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Emerald Group Publishing Ltd, 2020)
Purpose The purpose of this study is to work on heat transfer enhancement within different engineering cavities is the major aim of most technical solutions. Such intensification can be obtained by using smart liquids known as nanoliquids and solid fins. Therefore, free convective thermal transmission within square nanoliquid chamber under the influence of complex fins is studied. The considered fins are the combination of wall-mounted adiabatic fin and an adiabatic block over this fin. Design/methodology/approach Influences of the Rayleigh number, location of the local adiabatic block and nanoparticles concentration on liquid motion and energy transport are studied. Finite difference technique was used to solve the governing equations. Findings It has been ascertained that the energy transport intensification can be reached for the middle position of this local block within the cavity. Originality/value The main originality of this work is to use intermittent block in a nanofluid filled cavity under differentially heated conditions. One constant and location of one of the passive element is constant and other one is fixed, which is the intermittent block, is used to control heat and fluid flow. Thus, distance between blocks is allowed to control of the velocity and kinetic energy. In this way, temperature distribution also can be controlled inside the square cross-sectional closed space. Another originality of the work is to use nanoparticle added main flow for this geometry. Thus, energy efficiency can be controlled via adiabatic intermittent blocks without spending any extra energy.
Keywords: Nanofluid; Free convection; Finite difference method; Adiabatic fin; Differentially heated chamber; Local adiabatic block